The level of pregnancy and childbirth complications among the residents of front-line city of Kharkiv - I.V. Lakhno (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2024)
Background. The city of Kharkiv has been located in the area of armed conflict or the front-line zone since the beginning of the invasion of Russian troops. A part of the female reproductive-aged population constantly remains in Kharkiv which determines the possible negative impact of wartime stress.